Novel hybrid arithmetic-equilibrium optimizer as robust tuner for power system stabilizer (PSS) parameters in interconnected electrical power system - Imam Robandi; Mohamad Almas Prakasa; Muhammad Ruswandi Djalal; Shigemasa Takai; Arimbi Kumala Sari; Mochammad Adri Satria Musti (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
Nowadays, the metaheuristic approaches become popular in the optimal tuning parameters of power system controllers, especially Power System Stabilizers (PSS). Besides the easiness, the stochastic behavior in metaheuristic approaches needs further investigation to increase the quality of the offered optimal parameters. Thus, this paper proposes A Novel Hybrid Arithmetic-Equilibrium Optimizer (HAEO) as a robust tuner for PSS in the interconnected electrical power system. The algorithms are hybridized in unique ways to utilize the features in both Arithmetic Optimizer (AO) and Equilibrium Optimizer (EO). Hybridization is performed to improve the exploration ability by providing the widest optimal parameters possible. In benchmarking by the Friedman Ranking Test, the proposed algorithm shows a significant improvement in consistency and accuracy over the basic AO and EO. A wider-distributed optimal solution and better convergence are also offered by the proposed algorithm. Besides that, the application in the optimal tuning shows that the proposed algorithm can provide the best PSS parameters in different objective functions with better average and standard deviation values. The HAEO-PSS gives a significant overshoot suppression of 35 % to 57 %, while the settling time of the system is also improved by 7 % to 13 %. Overall, the HAEO-PSS is proven to improve the stability response of the interconnected electrical power system both in local and interarea responses.